HUBUNGAN ANTARA IKLIM PSIKOLOGIS TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - Muhammad Fajar Wahyudi Rahman; Anang Kistyanto (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, PT Rosan Permai is a family company initiated and founded in 1972 on street Keboan Sikep Gedangan, Sidoarjo. Engaged in the field of transportation services, both ankle and trailer truck rental and in sugar cane plantations. PT Rosan Permai is the only company in Sidoarjo regency which is officially registered as a company engaged in the delivery of goods and suppliers of sugar cane at sugar factories in the East Java area. The purpose of this study is to test and analyze the influence of psychological climate on employee performance through job satisfaction on employees of PT Rosan Permai Sidoarjo. This research is a causality study with a quantitative approach. The sampling technique used a saturated sample with a total of 44 respondents to employees of PT Rosan Permai Sidoarjo. The statistical analysis used in this study is Partial Least Square (PLS) with the help of smartPLS 3.0 software. The results of this study explain that the Psychological Climate has a positive and significant effect on Employee Performance. Psychological Climate has a positive and significant effect on Job Satisfaction. Job Satisfaction has a positive and significant effect on Employee Performance. Job Satisfaction mediates the influence of Psychological Climate on Employee Performance, but the results found that the Psychological Climate has a direct influence that is greater than the indirect effect on Employee Performance.